Public Participation in the Implementation of Forestry Decentralization in Indonesia - Tolo, Emilianus Yakob Sese (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
The implementation of decentralization in Indonesia brings two-fold effects. On the one hand, it has given more autonomy for regions to organize and manage their governmental affairs. However, on the other hand, regional autonomy causes problems in society, such as increased corruption, money politics, and environmental damage. By using descriptive-qualitative approach, the author evaluated the implementation of forestry decentralization in Indonesia with research focus in Manggarai and Central Maluku districts. This study found that the implementation of forestry decentralization ignored community involvement thus brought negative consequences such as the increasing damage to forest ecosystems and the declining public welfare. Therefore, in order to bring benefits for forest conservation and welfare of the community, forestry decentralization needs to fortify community involvement.